Agitation impacts fermentation performance as well as carbon and nitrogen metabolism in Saccharomyces cerevisiae under winemaking conditions. (14th February 2018) - Rollero, S.; Roberts, S.; Bauer, F.F.; Divol, B.
Abstract: Background and Aims: Under industrial conditions, fermenting juice is normally not mechanically agitated; thermodynamic forces will lead to some rotating motion of the medium. At laboratory scale, research aims to mimic industrial conditions using a standardised synthetic grape juice‐like medium. The level of agitation applied, however, to fermentations differs between the studies. In this study, we investigated the influence of agitation speed on fermentation parameters, including fermentation kinetics, yeast cell production and volatile aroma production. Methods and Results: These parameters were evaluated during fermentations under different agitation conditions. Agitation speed was found to significantly influence all the parameters monitored. In the evaluated conditions, a speed of 80 rpm was optimal for the production of fermentative aromas (lead to the highest production) while guaranteeing the complete and rapid fermentation and limiting the production of off‐flavours. Fermentation of a Chardonnay grape juice in 50 L tanks confirmed the results, and the panellists described the wine produced by the stirred fermentation as sweeter but it is likely that the panellists meant softer because the wines were dry. Conclusions: Agitation is an important parameter to control during fermentation under laboratory conditions. The data also suggest that the type and strength of agitation in commercial fermentations may have a more significant impact than previously thought. Significance of the Study: This study demonstrates that researchers must take into account the importance of agitation during their studies. Similarly, winemakers might consider constant agitation of their tanks.